Probing the volcanic-plutonic connection and the genesis of crystal-rich rhyolite in a deeply dissected supervolcano in the Nevada Great Basin: Source of the late eocene caetano tuff - Watts, Kathryn; Schmitt, Axel Karl (Journal of petrology, 2016)
Late Cenozoic faulting and large-magnitude extension in the Great Basin of the western USA has created locally deep windows into the upper crust, permitting direct study of volcanic and plutonic rocks within individual calderas. The Caetano caldera in north–central Nevada, formed during the mid-Tertiary ignimbrite flare-up, offers one of the best exposed and most complete records of caldera magmatism. Integrating whole-rock geochemistry, mineral chemistry, isotope geochemistry and geochronology with field studies and geologic mapping, we define the petrologic evolution of the magmatic system that sourced the >1100 km3 Caetano Tuff. The intra-caldera Caetano Tuff is up to ∼5 km thick, composed of crystal-rich (30–45 vol. %), high-silica rhyolite, overlain by a smaller volume of comparably crystal-rich, low-silica rhyolite. It defies classification as either a monotonous intermediate or crystal-poor zoned rhyolite, as commonly ascribed to ignimbrite eruptions. Crystallization modeling based on the observed mineralogy and major and trace element geochemistry demonstrates that the compositional zonation can be explained by liquid–cumulate evolution in the Caetano Tuff magma chamber, with the more evolved lower Caetano Tuff consisting of extracted liquids that continued to crystallize and mix in the upper part of the chamber following segregation from a cumulate-rich, and more heterogeneous, source mush. The latter is represented in the caldera stratigraphy by the less evolved upper Caetano Tuff. Whole-rock major, trace and rare earth element geochemistry, modal mineralogy and mineral chemistry, O, Sr, Nd and Pb isotope geochemistry, sanidine Ar–Ar geochronology, and zircon U–Pb geochronology and trace element geochemistry provide robust evidence that the voluminous caldera intrusions (Carico Lake pluton and Redrock Canyon porphyry) are genetically equivalent to the least evolved Caetano Tuff and formed from magma that remained in the lower chamber after ignimbrite eruption and caldera collapse. Thus, the Caetano Tuff contradicts models for the mutually exclusive origins of voluminous volcanic and plutonic magmas in the upper crust. Crystal-scale O isotope data indicate that the Caetano Tuff is one of the most 18O-enriched rhyolites in the Great Basin (δ18Omagma = 10·2 ± 0·2‰), supporting anatexis of local metasedimentary basement crust. Metapelite xenoliths in the Carico Lake pluton and ubiquitous xenocrystic zircons in the Caetano Tuff provide constraints for the anatexis process; these data point to shallow (<15 km) dehydration melting of a protolith similar to the Proterozoic McCoy Creek Group siliciclastic sediments in eastern Nevada, projected beneath Caetano in fault-stacked shelf sediments that were thickened during Mesozoic crustal shortening. Mean zircon U–Pb ages for different stratigraphic levels of the intra-caldera Caetano Tuff are 34·2–34·5 Ma, 0·2–0·5 Myr older than the caldera sanidine 40Ar/39Ar age of 34·00 ± 0·03 Ma, documenting protracted duration of assembly and homogenization of isotopically diverse upper crustal melts, followed by crystallization and zonation to generate the Caetano Tuff magma chamber. Sanidine rims in the least evolved Caetano Tuff and in the Carico Lake pluton and Redrock Canyon porphyry have sharply zoned Ba domains that point to crystal growth during magmatic recharge events. The recharge magma is inferred to have been compositionally similar to the Caetano Tuff magma, with increased Ba resulting from remelting of Ba-rich sanidine cumulates. Mush reactivation to generate the Caetano Tuff eruption was sufficiently rapid to preserve compositional gradients in the intracaldera ignimbrite, calling into question models that predict homogeneity as a prerequisite for remobilizing crystal-rich ignimbrite magmas.